Interaction, Surface Activity, and Application of Mixed Systems of Alcohol Ether Sulfate Anionic Surfactants with Multiple Ethylene Oxide Groups and Gemini Quaternary Ammonium Surfactant - Lin, Zengzi (Langmuir : the ACS journal of surfaces and colloids, 2024)
The surface activities and application properties for the mixtures of cationic surfactants tetramethylene-1,4-bis[N,N-bis(hydroxypropyl)-hexa/decyloxypropylammonium] bromide (GC10-P) and tetramethylene-1,4-bis[N,N-bis(hydroxyethyl)-hexa/decyloxypropylammonium] bromide (GC10-E) and anionic surfactant isomeric sodium fatty alcohol ether sulfates (iso-AE9S) were investigated using both the tensiometry and the conductometry. The interaction parameters and thermodynamic micellization parameters of GC10-P/iso-AE9S and GC10-E/iso-AE9S mixtures were evaluated by Clint-Rubingh and Motomura theoretical models. When the mole fraction of α1 for GC10-P/iso-AE9S mixed system was 0.2, the critical micelle concentration (CMC) reached a minimum of 1.61 × 10-4 mol/L, and the minimum critical micelle concentration of the GC10-E/iso-AE9S mixed system is 2.67 × 10-5 mol/L at α1 = 0.6. The CMC value of the mixed system is 1-2 orders of magnitude lower than that of any single component. The results indicate that the synergistic effects of the investigated mixed systems (evaluated by βm) are in order of GC10-P/iso-AE9S < GC10-E/iso-AE9S, with maximum βm values of -17.98 and -9.78, respectively. The change in zeta potential indicates that the poly(ethylene oxide) chain has weakened the charge density of the hydrophilic headgroup of the anionic surfactant. The interfacial tension at the oil-water interface in the mixed system of anionic/cationic surfactants is lower than that of any single component, exhibiting a higher interfacial activity. The mixed system exhibits a decreased contact angle and superior wetting ability over any single component, and it also enhances foam performance, emulsification performance, and degreasing performance